Portraying Monitoring in Federation of Heterogeneous Clouds - Ekta Dureja (International Journal on Orange Technologies, 2022)
The heterogeneity of infrastructure, heterogeneity of interface, heterogeneity of objectives are few inherent features of a federation of clouds. To ensure the smooth and supportive interaction between various components or entities of the federation can only be ensured with the constant monitoring of each unit of federation. Monitoring in different clouds is undertaken in different styles and purpose. Commercial cloud like Amazon monitors for the optimal performance of resources. Microsoft Azure Cloud does monitor various activities for the user. Not only the purpose, but also the functionality of monitoring is different. The variety of methods and metrics for monitoring, objectives of monitoring in various federations motivated this study of monitoring subsystem. This analysis of monitoring component in diverse federation architectures is done with a view to highlight the effect of monitoring system in major federation architectures such as FCM (Federated Cloud Management).